Dataset shift in machine learning - Quiñonero-Candela, Joaquin (MIT Press, 2009)
This work is an overview of recent efforts in the machine learning community to deal with dataset and covariate shift which occurs when test and training inputs and outputs have different distributions.
Keywords: Machine learning.; elektronické knihy; electronic books